Heat‐Driven Iontronic Nanotransistors. Issue 7 (25th January 2023) - Prete, Domenic; Colosimo, Alessia; Demontis, Valeria; Medda, Luca; Zannier, Valentina; Bellucci, Luca; Tozzini, Valentina; Sorba, Lucia; Beltram, Fabio; Pisignano, Dario; Rossella, Francesco
Abstract: Thermoelectric polyelectrolytes are emerging as ideal material platform for self‐powered bio‐compatible electronic devices and sensors. However, despite the nanoscale nature of the ionic thermodiffusion processes underlying thermoelectric efficiency boost in polyelectrolytes, to date no evidence for direct probing of ionic diffusion on its relevant length and time scale has been reported. This gap is bridged by developing heat‐driven hybrid nanotransistors based on InAs nanowires embedded in thermally biased Na + ‐functionalized (poly)ethyleneoxide, where the semiconducting nanostructure acts as a nanoscale probe sensitive to the local arrangement of the ionic species. The impact of ionic thermoelectric gating on the nanodevice electrical response is addressed, investigating the effect of device architecture, bias configuration and frequency of the heat stimulus, and inferring optimal conditions for the heat‐driven nanotransistor operation. Microscopic quantities of the polyelectrolyte such as the ionic diffusion coefficient are extracted from the analysis of hysteretic behaviors rising in the nanodevices. The reported experimental platform enables simultaneously the ionic thermodiffusion and nanoscale resolution, providing a framework for direct estimation of polyelectrolytes microscopic parameters. This may open new routes for heat‐driven nanoelectronic applications and boost the rational design of next‐generation polymer‐based thermoelectric materials. Abstract : A novel class of thermally‐driven, hybrid nanotransistors based on InAs nanowires is developed. Semiconductor nanostructure devices are embedded in Na + ‐functionalized (poly)ethyleneoxide and allow for extracting the parameters featuring ionic thermodiffusion. Reported results open new perspectives for heat‐driven nanoelectronic applications and boost the rational design of next‐generation polymer‐based thermoelectric materials.